Antibacterial abilities of intestinal microflora in cultured and wild Atlantic salmon (Salmo salar L.) fry - Skrodenytė-Arbačiauskienė, Vesta (2005)
Bacterial strains were isolated from the intestinal tract of cultured and wild Atlantic salmon (Salmo salar L.) fry and examined for their antibacterial abilities against Escherichia coli, Staphylococcus aureus, Bacillus subtilis, Candida albicans and ten Flavobacterium columnare strains causing columnaris disease. A total of 150 isolates from the intestinal tract of Atlantic salmon were classified into Acinetobacter, Aeromonas, Enterobacteriaceae, Plesiomonas, Pseudomonas and Micrococcus. Aeromonas and Entero-bacteriaceae were dominant taxonomic groups in the intestinal tract of Atlantic salmon fry. All tested taxonomic groups from the intestinal tract of cultured Atlantic salmon exhibited antibacterial activity of 64 to 100% against five target strains. Antibacterial abilities of intestinal microflora of Atlantic salmon from the Žeimena River against the tested pathogenic bacteria ranged from 0 to 15%. The results suggest that intestinal bacteria may inhibit some opportunistic pathogens and the fish pathogenic bacteria F. columnare - the causative agent ofcolumnaris disease - by producing antibacterial substances depending on environmental conditions.